Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Lulusan Di MA Daruttamam NW Tampih - M. Saipul Watoni; Zakaki; Muhammad Rodi (Pendidikan Al-Gafari, 2023)
The low role head school in increase quality graduate of resulted not enough its effective head school in give motivation and support to teachers and students so the strategy is carried out head school in increase quality graduate of Still low quality graduate in level school elementary, intermediate, and above. For it, researcher try stage purposeful research For know the Role of Leadership Head School in Improving the Quality of Graduates at Ma Daruttamam Nw View, where focus study This is, What just role leadership head school in increase quality Daruttamam NW Tampih MA graduates.? What just the strategy applied head school in increase quality Daruttamam NW Tampih MA graduates?. How quality graduates produced by MA Daruttamam NW Tampih.? As for master from study This is For know and explain What just role leadership head school in increase quality Daruttamam NW Tampih MA graduate. For know and explain What only the strategy carried out by the head MA Daruttamam NW Tampih school in increase quality graduates. For know How quality Daruttamam NW Tampih MA graduate. In the study this, is used study qualitative with type field research research (research field). Whereas in data collection is carried out with method interview, observation and documentation whatever after the data is collected Then analyzed To use check its validity. In research This after he did study so researcher get a number of answer from formula problem that researchers put with conclusion that important for a head school or madrasa for have a good strategy For print good madrasa graduates.